A constitutive model for paperboard including wrinkle prediction and post-wrinkle behavior applied to deep drawing. (15th June 2017) - Linvill, Eric; Wallmeier, Malte; Östlund, Sören
Highlights: During the deep drawing of paperboard, many wrinkles initiate and propagate. A 1-D hinge model is used to describe the mechanical behavior of wrinkled paperboard. The hinge model is incorporated into a continuum 3-D elasto-plastic material model. Both 1-D and 3-D models are validated against experiments. The developed models are utilized in a parametric study of the deep drawing process. Abstract: A simple, one-dimensional model for perfectly plastic hinges, utilizing a hinge yield strength, was applied to wrinkled paperboard and validated. The hinge model was incorporated into a three-dimensional constitutive model of paperboard including wrinkle initiation, wrinkle compression, as well as tensile re-loading of wrinkled paperboard. The constitutive model enables the explicit finite element simulation of the deep drawing of a non-creased paperboard blank, including spring-back after the forming process. The results of the simulated deep-drawing process were validated against experimental deep-drawn paperboard cups, and parametric studies were conducted to investigate the effects of process and material parameters on three different quality measures (spring-back magnitude, asymmetry, and punch force). In addition to aiding the development of the simulation of paperboard deep drawing, the hinge yield strength was also found to be the only studied material property which could simultaneously improve all three quality measures.